Childhood nature connection and constructive hope: A review of research on connecting with nature and coping with environmental loss - Chawla, Louise (People and Nature, 2020)
Within a generation, children's lives have largely moved indoors, with the loss of free-ranging exploration of the nearby natural world, even as research indicates that direct experiences of nature in childhood contribute to care for nature across the life span. In response, many conservation organizations advocate connecting children with nature, and there has been rising interest in measuring young people's connectedness with nature, understanding how it relates to their well-being and stewardship behaviour and creating programs to increase connection. This article reviews the literature on these topics, covering both quantitative and qualitative studies. It notes that this research emphasizes positive experiences and emotions, even as global environmental changes and biodiversity loss accelerate. Young people's emotions of worry, frustration and sadness as they learn about environmental degradation also express their understanding that they are connected to the biosphere. Therefore this review includes research on how young people cope with information about large-scale environmental problems, and it identifies practices to sustain hope. The review concludes by suggesting how research on connection with nature and coping with environmental change can benefit from integration. A free Plain Language Summary can be found within the Supporting Information of this article.
Keywords: adolescent; biodiversity loss; child; climate change; environmental identity; hope; nature connection; proenvironmental behaviour; wellbeing